(untitled) (The International Journal for Scientific Research, 2023)
This study aimed to identify the most important barriers that women in Yemen face in accessing and using information and communications technology considering the technological and information revolution that we are experiencing today in order to find solutions to address them. The study population consists of women working in the organized economy, given that this segment of women has received a sufficient amount of education and has overcome the obstacles related to women’s work. The study also focused on the governorates of Sana’a and Aden, as they are major centers for government institutions and private companies and have a better infrastructure compared to other governates. The results revealed that infrastructure, especially regarding Internet speed and weak network coverage, constitute the most important barriers to using the Internet. The results also revealed that the most prominent social barrier is the phenomenon of electronic blackmail, which has recently become widespread in Yemeni society. The results also showed that women’s education and work enhanced their status in society and gave them a great deal of freedom and the absence of parental interference in the technological devices and tools that they possess, in addition to helping them bear the costs of purchasing and using these devices without the need for others, and their possession of technical skills that help them in accessing and using them. Accordingly, the study presented a set of recommendations and proposals that would help overcome these barriers and improve women’s access to information and communications technology and their use of it in a way that benefits them.